SAT0021 Innate lymphoid cells are not a main source of il-17a in the inflamed spondyloarthritis joint. (12th June 2018) - Yeremenko, N.; Blijdorp, I.C.J.; Van Mens, L.J.J.; Menegatti, S.; Chen, S.; Hreggvidsdottir, H.S.; Noordenbos, T.; Latuhihin, T.E.; Bernink, J.H.; Rogge, L.; Spits, H.; Baeten, D.L.P.
Abstract : Background: Clinical trials of the anti-IL-17A antibody secukinumab demonstrated the crucial role of IL-17A cytokine in the pathogenesis of spondyloarthritis (SpA), however, its cellular source in this condition remains controversial. Group 3 innate lymphoid cells (ILC3s) have been recently identified in a number of different tissues as potent producers of proinflamatory cytokines, including IL-17A and IL-22. Objectives: In this study we set out to characterise the presence and composition of ILCs and investigate whether these cells are the important source of IL-17A in the synovial tissue of patients with SpA. Methods: Matched synovial tissue (ST), synovial fluid (SF) and peripheral blood (PB) were obtained from SpA and rheumatoid arthritis (RA) patients with actively inflamed knee joints. ILCs subsets were characterised by flow cytometry. Gene expression analysis at the single-cell level was performed directly ex vivo and after stimulation with PMA ionomycin. IL-17A ELISPOT assay was used to detect IL-17A-secreting cells. Results: Analysis revealed that ILCs, and particularly NKp44-positive ILC3s, are expanded in the inflamed arthritic joint. Single cell expression analysis revealed that ST ILCs are clearly distinguishable from ST T cells and from their PB counterparts. We detected expression of Th17 signature transcripts RORC, AHR and IL-23R in the notable fraction of ST ILC3s. Furthermore these cells were capable to induce IL-22, but not IL-17A expression in response to. in vitro re-stimulation Conclusions: We demonstrate in this study that ILC3s are absolutely and relatively enriched in the synovial joint of patients with SpA, however these cells are not a significant source of IL-17A cytokine in this pathology. Disclosure of Interest: None declared